Study on Wear Characteristics of Coal Drain Chute for Open Pit Mine - Xuewei TAO; Guoliang XIE; Mingxiang GUO; Zirun YANG; Yue HUANG; Runjie GONG (Medžiagotyra)
With the advancement of social science and technology and the escalating demand for resources, the utilization rate and load of mechanical equipment in diverse industries have become increasingly prominent. Mechanical malfunctions occur frequently, especially in material transportation, causing substantial economic losses. Mechanical wear has emerged as the principal cause of mechanical equipment failure; hence, studying the wear of particles and transportation machinery is of paramount importance. This paper utilizes the discrete element method and numerical simulation approach to investigate the influence of mechanical structure alterations on the wear of discharge chutes in coal conveyor systems. The results reveal that in terms of speed, reducing the conveyor belt speed has negligible effects on the falling trajectory and distribution characteristics of the materials but reduces the frequency of contact between the materials and the chute surface, thereby diminishing the tangential force exerted by the materials on the chute. The tangential cumulative force plays a crucial role in the wear of the chute by granular particles and can effectively alleviate the wear of the chute. With respect to the inclination angle of the conveyor belt, when increasing the angle clockwise, the influence on the falling trajectory and distribution characteristics is relatively minor, and the falling speed of the materials will accelerate. Nevertheless, the wear of the chute will decrease as the inclination angle increases. When increasing the inclination angle counterclockwise, the falling trajectory and distribution characteristics are significantly affected, and the materials will tend to concentrate, and the falling speed will decelerate, resulting in a substantial reduction in chute wear. These discoveries provide theoretical underpinnings for reducing equipment wear and optimizing coal transportation equipment.